The Role of Vitamin in the Nutrition of Premature Infants - Ruslie, Riska Habriel (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Vitamin is an organic compound required as a vital nutrient in tiny amounts. Premature infants are at risk of vitamin deficiency than mature infants, due to inadequate transplacental transport, inadequate storage, and increased tissue utilization. Infant that are born prematurely have a low amount of stored vitamin in their body. The amount that is stored is quickly used as the infant grows. So, vitamin is a very important for development of premature infants. In this review examines the role of vitamin in the nutrition of premature infants (Sains Medika, 4(1):97-111).